Republic of Azerbaijan : Report on the Observance of Standards and Codes; Data Module, Response by the Authorities, and Detailed Assessment Using the Data Quality Assessment Framework (DQAF). (IMF Staff Country Reports; Country Report, 2008)
This Data Module of the Report on the Observance of Standards and Codes (ROSC) provides an assessment of Azerbaijan's macroeconomic statistics against the Special Data Dissemination Standard (SDDS) complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework (DQAF), July 2003. The assessment reveals that Azerbaijan's Consumer Price Index (CPI) meets Special Data Dissemination Standard (SDDS) specifications for coverage, periodicity, and timeliness. The CPI has good data sources for both weights and prices, based on well-designed household and retail establishment surveys.